SELECTION OF VARIETIES AND HYBRIDS OF TABLE BEET FOR THE CONDITIONS OF THE LEFT BANK FOREST STEPPE OF UKRAINE - Басюк, Сніжана (SWorldJournal, 2023)
Table beetroot (Веta vulgaris horensis L.) occupies one of the leading positions in the group of vegetables in terms of its taste and medicinal properties, it belongs to the vegetable group of the "borscht set".There are 16 hybrids and 18 varieties with